Wear-aware adaptive routing for networks-on-chips - Vitkovskiy, Arseniy; Soteriou, Vassos; Gratz, Paul V. (My University, 2015)
Chip-multiprocessors are facing worsening reliability due to prolonged operational stresses, with their tile-interconnecting Network-on-Chip (NoC) being especially vulnerable to wearout-induced failure. To tackle this ominous threat we present a novel wear-aware routing algorithm that continuously considers the stresses the NoC experiences at runtime, along with temperature and fabrication process variation metrics, steering traffic away from locations that are most prone to Electromigration (EM)- and Hot-Carrier Injection (HCI)-induced wear. Under realistic applications our wear-aware algorithm yields 66% and 8% average increases in mean-time-to-failure for EM and HCI, respectively.
Keywords: Electromigration (EM); Hot-Carrier Injection (HCI); Lifetime; Network-on-chip; Reliability; Routing algorithm